Sentencing Principles and Guidelines In International Criminal Law: The Contradictory Assumptions and Methods of Reasoning in International Criminal Law (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The general narrative of internationalcriminal law (ICL) declares that the system adheres in an exemplary manner tothe fundamental principles of a liberal criminal justice system. Recentscholarship has increasingly questioned the adherence of various ICL doctrinesto such principles. This study scrutinizes the discourse of ICL – theassumptions and forms of argumentation that are regarded as sound reasoningwith appropriate liberal aims. This study argues that ICL, in drawing onnational criminal law and international human rights law, absorbedcontradictory assumptions and methods of reasoning. The study explores threemodes by which the assumptions of human rights liberalism subtly undermine thecriminal law liberalism to which the system aspires. These modes includeinterpretive approaches, substantive and structural conflation, and ideologicalassumptions. The identity crisis theory helps to explain how a system thatstrives to serve as a model for liberal criminal justice systems has come toembrace illiberal doctrines that contradict the system’s fundamentalprinciples.